The OVERWIEV OF ANTIVIRAL DRUGS AGAINST SARS-CoV-2 FOR THE TREATMENT OF COVID-19: DRUGS AGAINST SARS-CoV-2 - Anderluh, Marko; Tomašič, Tihomir; Jakopin, Žiga (Acta medicae Medianae, 2020)
The new coronavirus SARS-CoV-2 has quickly spread all over the globe causing a global pandemic. The intrinsic properties of the virus make it potentially fatal, as COVID-19 disease severity varies among individuals with currently unknown background. The world community is thus in a desperate need for novel antiviral drugs against SARS-CoV-2. In this work, we focus on macromolecular targets present on SARS-CoV-2 virus as potential targets for antiviral drugs. In the continuation, we offer a brief presentation of drugs or drug candidates that act directly on virus life cycle and have promising effects in COVID-19 therapy.
Keywords: antiviral drugs; SARS-CoV-2; COVID-19; coronavirus